The Constant and the Variable in the Kurdish Singing between the Past and Present: كونا قادر محمد (Al-Academy, 2020)
This research is interested in studying the constant and the variable within the signing reality in Iraqi Kurdistan region, and the researcher tries to tackle the importance of this topic within a search that serves the Kurdish culture, and contribute to its intellectual settlement, and introducing it to centers concerned with studying singing and music science in any civilized environment, whether inside or outside the territory of Kurdistan region. We see that this research which dealt with the topic (the constant and the variable in the Kurdish signing between the past and the present) deserves research and investigation for all its causes, being one of the academic necessities that contribute in identifying the historic artistic and singing depth in the Kurdish heritage. The researcher used resources and interviews, which showed its status and the variables inside her community, in addition to its manifestations in front of the environmental reality. The researcher adopted the descriptive approach which is based on analyzing and criticizing the musical and singing phenomena. In order to achieve the research objective, based on discussing the facts and opinions about what is familiar in the subject of the constant and the variable in the Kurdish singing, the research consists of four chapters. The first chapter included the research methodological framework, represented by the research problem and significance. The second chapter: the theoretical framework represented by the following topics ( the singing art between the past and the present, the reasons of the constant and variable in singing, and the reality of the singing art in the Iraq Kurdistan region). The third chapter included the research methodology, and the analysis of a number of samples. The fourth chapter included the results and recommendations, then put forward a number of recommendations and suggestions and finally a list of sources.